Acute effect of endurance exercise on human milk insulin concentrations: a randomised cross-over study - Holm, Rebecca Lyng; Holmen, Mads; Sujan, Md Abu Jafar; Giskeødegård, Guro F.; Moholdt, Trine (Frontiers in Nutrition, 2025)
IntroductionInsulin is present in human milk and its concentration correlates with maternal circulating levels. Studies on the association between human milk insulin concentrations and infant weight or growth show conflicting results, but some studies indicate that higher insulin concentrations in the milk can promote infant weight gain. Circulating levels of insulin decrease acutely after exercise, but no prior study has investigated the acute effect of exercise on human milk insulin concentrations. Our aim was to determine the acute effects of two endurance exercise protocols on human milk insulin concentration in exclusively breastfeeding individuals.MethodsIn a randomised cross-over trial, 20 exclusively breastfeeding participants who were 6–12 weeks postpartum completed three conditions on separate days: (1) moderate-intensity continuous training (MICT), (2) high-intensity interval training (HIIT), and (3) no activity (REST). Milk was collected before exercise/rest (at 07:00 h), immediately after exercise/rest (11:00 h), 1 h after exercise/rest (12:00 h), and 4 h after exercise/rest (15:00 h). We determined insulin concentrations in the milk using enzyme-linked immunosorbent assay and compared insulin concentrations after MICT and HIIT with REST using a linear mixed model with time-points and the interaction between time and condition as fixed factors.ResultsWe detected insulin in all 240 samples, with an average concentration of 12.3 (SD 8.8) μIU/mL (range 3.2–57.2 μIU/mL). There was no statistically significant effect of exercise on insulin concentration, but a tendency of reduced concentrations 4 h after HIIT (p = 0.093). There was an overall effect of time at 11:00 h and 15:00 h. In the fasted sample obtained at 07:00 h, the concentration was 9.9 (SD 7.2) μIU/mL, whereas the concentration was 12.7 (SD 9.0) μIU/mL at 11:00 h (p = 0.009), and 15.0 (SD 11.7) μIU/mL at 15:00 h (p < 0.001).ConclusionOne session of endurance exercise, either at moderate- or high intensity, had no statistically significant effect on human milk insulin concentration. Future research should determine the effect of regular exercise on insulin in human milk and potential impact for infant health outcomes.Clinical trial registrationClinicalTrials.gov, identifier NCT05042414.